Mythical Symbols in the Contemporary Poetry of Basra 2003-2021 - . Alwan Al-Kinani, Assist . Prof. Najat; Abdul-Ridha Isyud, Prof. Dr. Sabah (Basra studies journal, 2023)
Some contemporary poets in Basra managed to employ mythical symbols in their poems by transmitting through them some of their poetic experiences. As well as adding aesthetic elements and components to the poetic text. They were also able to interact with the symbolic signifier that stems from those myths for expressing their contemporary experiences in sense of reality.